EKRANISASI NOVEL 3600 DETIK KARYA CHARON KE DALAM FILM 3600 DETIK KARYA SUTRADARA NAYATO FIO NAULA - Ratna Sari; Dian Hartati (Jurnal Ilmiah Wahana Pendidikan, 2023)
The ekranization theory by Eneste (1991), which is used to analyze the novel "3600 Detik" by Charon and the film "3600 Detik" directed by Nayato Fio Naula, will discuss the processes of reduction, addition, and variation changes in both literary works. This research aims to determine the result of adapting Charon's novel "3600 Detik" into the film "3600 Detik" directed by Nayato Fio Naula. The method used in this study is descriptive qualitative. Data collection techniques employed include observation, note-taking, watching, and comparison. The research findings reveal reductions in the setting, the addition of one character, and variation changes in several scenes, such as alterations to Leon's illness, Leon's father's occupation, the music storekeeper, the location of Leon's last breath, the presence of Sandra's parents at Leon's funeral, and the ending of the story experienced by Sandra. Overall, the ekranization of Charon's novel "3600 Detik" and the film "3600 Detik" directed by Nayato Fio Naula do not fundamentally alter the core story of both works. Both the novel and the film have captivating elements that can indulge readers and viewers in the presented story. The author successfully captivates readers with the plot, attracting the attention of the director to adapt the novel into a film. The director manages to balance the novel's story when translating it into a film, ensuring that every detail is considered to convey the story to the audience without altering its essence.